Correction of Nonlinear Frequency Sweep in Frequency-Modulated Continuous-Wave Laser Range Sensor - Soo-Yong Jung; Seong Ro Lee; Chang-Soo Park (International Journal of Distributed Sensor Networks)
We propose a linearization method for reducing the effect of nonlinear frequency sweep in a frequency-modulated continuous-wave (FMCW) based laser range sensor. In FMCW laser range sensors, nonlinear frequency sweep can severely degrade the measurement accuracy because it gives the system ambiguity when determining the target range. In general, voltage controlled oscillators (VCO) which are used for frequency modulation show nonlinear frequency sweep property even though the input voltage signal is a linear ramp signal. To solve this problem, we adopt an additional fixed delay structure to extract the nonlinearity and compensate it. The proposed linearization method has been worked out through the numerical process and the simulation, and this method effectively eliminates the nonlinear frequency sweep problem.